2016
DOI: 10.3892/ijo.2016.3562
|View full text |Cite|
|
Sign up to set email alerts
|

Receptor for activated C kinase 1 (RACK1) promotes the progression of OSCC via the AKT/mTOR pathway

Abstract: Our previous study suggested that receptor for activated C kinase 1 (RACK1) contribute to the progression of oral squamous cell carcinoma (OSCC). The aim of this study is to elucidate the mechanism by which RACK1 regulates cell growth in OSCC using in vitro and in vivo models. The effects of RACK1 knockdown with lentivirus based shRNA in stable cell lines were evaluated by Q-PCR and western blot analysis. RACK1 silencing effects on the cell cycle in OSCC cells were detected by flow cytometry and western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…We also firstly discovered that the protein levels of G1/S transition key regulators, Cyclin D1 and CDK6, were remarkably reduced when RACK1 was silenced both in U87 and U251 cells. Concordantly with our results, Li et al reported that RACK1 was highly expressed in pancreatic ductal adenocarcinoma (PDAC) and could induce G1/S cell cycle arrest by decreasing the expression of Cyclin D1 [31], while Zhang et al reported that overexpression of RACK1 contributed to the progression of oral squamous cell carcinoma (OSCC) and stable silencing of RACK1 resulted in a distinct G1 and G2 phase arrest by downregulating Cyclin B1 and Cyclin D1 [33]. …”
Section: Discussionsupporting
confidence: 90%
“…We also firstly discovered that the protein levels of G1/S transition key regulators, Cyclin D1 and CDK6, were remarkably reduced when RACK1 was silenced both in U87 and U251 cells. Concordantly with our results, Li et al reported that RACK1 was highly expressed in pancreatic ductal adenocarcinoma (PDAC) and could induce G1/S cell cycle arrest by decreasing the expression of Cyclin D1 [31], while Zhang et al reported that overexpression of RACK1 contributed to the progression of oral squamous cell carcinoma (OSCC) and stable silencing of RACK1 resulted in a distinct G1 and G2 phase arrest by downregulating Cyclin B1 and Cyclin D1 [33]. …”
Section: Discussionsupporting
confidence: 90%
“…To uncover the biological function of RACK1 during macrophage recruitment in OSCC, both cell migration and invasion assays were performed. First, a stable HSC‐3 cell line with low RACK1 expression (sh‐RACK1) and a stable HSC‐4 cell line with RACK1 overexpression (OE‐RACK1) were generated as previously described (Zhang et al , ). Then, we investigated the migration abilities of macrophages after coculture with conditioned media from OSCC cells with different levels of RACK1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…THP‐1 monocytes were cultured in RPMI medium supplemented with 10% FBS. The generation of stable HSC‐3 cells with low RACK1 expression (sh‐RACK1) and HSC‐4 cells with RACK1 overexpression (OE‐RACK1) was performed as previously described (Zhang et al , ). All cells were cultured under a humidified atmosphere with 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al . reported that stable RACK1 knockdown downregulated Cyclin B1 and Cyclin D1 and promoted G1 and G2 phase arrest in oral squamous cell carcinoma [47]. Interestingly, RACK1 has the opposite effect in colon cancer cells; RACK1 overexpression delays passage of HT-29 cells through G1 and mitotic checkpoints by suppressing Src-mediated Sam68 phosphorylation and maintaining the active state of CDK1-cyclinB [48, 49].…”
Section: Discussionmentioning
confidence: 99%